2017
DOI: 10.1123/ijspp.2016-0403
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Training and Competition Loads in Endurance Sports: Methods and Applications

Abstract: Training quantification is basic to evaluate an endurance athlete's responses to training loads, ensure adequate stress/recovery balance, and determine the relationship between training and performance. Quantifying both external and internal workload is important, because external workload does not measure the biological stress imposed by the exercise sessions. Generally used quantification methods include retrospective questionnaires, diaries, direct observation, and physiological monitoring, often based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 42 publications
2
113
0
9
Order By: Relevance
“…Nevertheless, to date no single measure has been identified that can accurately quantify the fitness and fatigue responses to training or predict performance. 1,10,11 While agreement may exist relating to the principal findings and recommendations in this paper, we acknowledge that the decision on which monitoring tools or techniques to use should remain with the professionals working in sport. This will allow …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, to date no single measure has been identified that can accurately quantify the fitness and fatigue responses to training or predict performance. 1,10,11 While agreement may exist relating to the principal findings and recommendations in this paper, we acknowledge that the decision on which monitoring tools or techniques to use should remain with the professionals working in sport. This will allow …”
Section: Resultsmentioning
confidence: 99%
“…Key features of such systems should include ease of use and intuitive design, efficient result reporting, ability to be used remotely, translatability of data into simple outcomes, flexibility and adaptability for different sports, ability to simply and efficiently identify meaningful change, an assessment of cognitive function, and capability of providing both individual and group responses. 1,10 …”
Section: Endurance Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Significantly different from total time spent in intensity zone quantified using PO 2 Sigificantly different from total time spent in intensity zone quantified using HR "Training intensity distribution in road cyclists: objective versus subjective measures" by Sanders D, Myers T, Akubat I. Abbreviations: sRPE, session rating of perceived exertion; HR, heart rate; PO, power output.…”
Section: Figures and Tablesmentioning
confidence: 99%
“…1 To have an impact on performance, coaches must have an idea of the nature of the relationship between the training dose (or training load) and the training outcome or response. 2 Ultimately, it is the internal training load that will determine the training outcome. 3 In a training plan, the training load will be manipulated and this is most frequently done by adjusting the distribution of training intensity throughout the training plan.…”
Section: Introductionmentioning
confidence: 99%